Effect of active follow-up of women with previous cesarean delivery on uptake of timely safe obstetric and surgical care: Comparison between pre-intervention and intervention cohorts in Rwanda - Josée Uwamariya; Gloriose Abayisenga; Ntwali Ndizeye; Fidele Nkurunziza; Albert Bisore Ngemanyi; Christian Mazimpaka; Jean Maurice Munyabarenzi; Rosine Bigirimana; Gilbert Rukundo; François Regis Cyiza; Farhad Khan; Renae Stafford; et al. (PLoS ONE, 2025)
Introduction The rate of cesarean delivery (CD) in Rwanda has increased significantly from 2.2% in 2000 to 15.6% in 2020. Given increasing risks in subsequent pregnancy following CD it is important that women who have had a prior cesarean section plan and schedule CD in later pregnancies. This study assessed the effectiveness of the USAID MOMENTUM Safe Surgery in Family Planning and Obstetrics intervention in reducing emergency CDs among women with previous CDs. Methods We conducted a cohort study in four public hospitals and 64 health centers across Rwanda, comparing two non-parallel cohorts: a pre-intervention cohort (December 2021–February 2022) and an intervention cohort (November 2022–May 2023). Exploratory data analysis and logistic regression were conducted to analyze the emergency CD rate and any associated factors. Results The pre-intervention group comprised 212 women, whereas the intervention group involved 283 women, of whom 189 were included in the analysis. Among the 189 women in the intervention group, 87.3% reported to the hospital within five days post-referral when they were first called. The percentage of women who consulted for a delivery plan within 36–38 weeks of gestation increased from 37.6% in the pre-intervention group to 62.4% in the intervention group. Consequently, in the adjusted logistic regression model, there was still a significant association between the intervention and reduced odds of emergency CD, with a 81% reduction in the odds of delivery by emergency CD (0.187; 95% CI: [0.115; 0.298]) compared to pre-intervention. Conclusion This study demonstrates the effectiveness of an active follow-up intervention in promoting delivery planning and reducing emergency CD rates among pregnant women with previous CD scars. The comprehensive intervention, including tailored education and personalized phone conversations around the delivery period, appears to have contributed to increased awareness and motivation for women to seek timely care at the hospital for delivery planning.